2014
DOI: 10.14348/molcells.2014.0078
|View full text |Cite
|
Sign up to set email alerts
|

Shear Stress and Atherosclerosis

Abstract: Hemodynamic shear stress, the frictional force acting on vascular endothelial cells, is crucial for endothelial homeostasis under normal physiological conditions. When discussing blood flow effects on various forms of endothelial (dys)function, one considers two flow patterns: steady laminar flow and disturbed flow because endothelial cells respond differently to these flow types both in vivo and in vitro. Laminar flow which exerts steady laminar shear stress is atheroprotective while disturbed flow creates an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
93
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(100 citation statements)
references
References 56 publications
0
93
0
7
Order By: Relevance
“…This force modulates endothelial function and, if altered, exerts a detrimental effect on cardiovascular health. However, little is known about the endothelium-specific response to wall shear stress within the pulmonary vasculature and its role in the pathogenesis and progression of pulmonary vascular diseases (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…This force modulates endothelial function and, if altered, exerts a detrimental effect on cardiovascular health. However, little is known about the endothelium-specific response to wall shear stress within the pulmonary vasculature and its role in the pathogenesis and progression of pulmonary vascular diseases (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has provided new insights into the cellular mechanisms of flow-dependent regulation of vascular function that leads to cardiovascular events such as atherosclerosis, atherothrombosis, and myocardial infarction. 25) Endothelial dysfunction caused by disturbed flow is thought to be one of the primary culprits in the progression of atherosclerosis. Time rate of BP variation, as an index of shear stress in the vessel wall, may pose a great threat to endothelial cells in certain signal pathways, including inflammation and oxidative stress, and further promote platelet aggregation and plaque formation.…”
Section: Discussionmentioning
confidence: 99%
“…The disturbance of laminar blood flow in certain nonlinear vascular segments is thought to facilitate atherosclerotic progression through promoting shear stress-induced endothelial dysfunction [21,22]. In particular, Heo et al [23] demonstrated that disturbed laminar flow downregulates endothelial cell production of the enzyme eNOS.…”
Section: Discussionmentioning
confidence: 99%